2021
DOI: 10.2196/18198
|View full text |Cite
|
Sign up to set email alerts
|

Conceptualizing Usability for the eHealth Context: Content Analysis of Usability Problems of eHealth Applications

Abstract: Background Usability tests can be either formative (where the aim is to detect usability problems) or summative (where the aim is to benchmark usability). There are ample formative methods that consider user characteristics and contexts (ie, cognitive walkthroughs, interviews, and verbal protocols). This is especially valuable for eHealth applications, as health conditions can influence user-system interactions. However, most summative usability tests do not consider eHealth-specific factors that c… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
17
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 28 publications
(17 citation statements)
references
References 54 publications
0
17
0
Order By: Relevance
“…Additionally, the HUBBI has some overlap in terms of measurement items in other instruments, like the PSSUQ ( The system gave error messages that clearly told me how to fix problems ), MAUQ ( overall , I am satisfied with this system ) and Health-ITUES ( the information provided with [system] is clear) . But while each of these questionnaires contain some elements of the HUBBI, they do not evaluate the full scope of eHealth usability , as covered in the ontology for eHealth usability [ 15 ]. In this ontology, 70% of the factors are general usability factors that are relevant to all digital technologies regardless of their specific domain.…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…Additionally, the HUBBI has some overlap in terms of measurement items in other instruments, like the PSSUQ ( The system gave error messages that clearly told me how to fix problems ), MAUQ ( overall , I am satisfied with this system ) and Health-ITUES ( the information provided with [system] is clear) . But while each of these questionnaires contain some elements of the HUBBI, they do not evaluate the full scope of eHealth usability , as covered in the ontology for eHealth usability [ 15 ]. In this ontology, 70% of the factors are general usability factors that are relevant to all digital technologies regardless of their specific domain.…”
Section: Discussionmentioning
confidence: 99%
“…The other 30% are eHealth-specific factors that are essential for evaluating usability of eHealth applications. Likewise, in the work by Broekhuis et al [ 15 ] an analysis of the usability issues identified within eight datasets was presented in which the division of general usability issues versus eHealth-specific usability issues (based on the ontology mentioned before) also displayed this 70%-30% split. The HUBBI reflects this 70%-30% division, as five out of the 18 items are eHealth-specific items while the remaining items are more generally formulated.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations